Systems Approach Reveals Nuclear Factor Erythroid 2-Related Factor 2/Protein Kinase R Crosstalk in Human Cutaneous Leishmaniasis - Vivarini, Áislan de Carvalho; Calegari-Silva, Teresa Cristina; Saliba, Alessandra Mattos; Boaventura, Viviane Sampaio; França-Costa, Jaqueline; Khouri, Ricardo; Dierckx, Tim; Dias-Teixeira, Karina Luiza; Fasel, Nicolas; Barral, Aldina Maria Prado; Borges, Valéria Matos; Van Weyenbergh, Johan; et al. (Frontiers in Immunology, 2017)
Leishmania parasites infect macrophages, causing a wide spectrum of clinical manifestations ranging from cutaneous to visceral forms. In search of novel therapeutic targets, we performed comprehensive in vitro and ex vivo mapping of the signaling pathways upstream and downstream of antioxidant transcription factor Nrf2 in cutaneous leishmaniasis (CL), by combining functional assays in human and murine macrophages with a systems biology analysis of in situ (skin biopsies) CL patient samples. First, we show the PKR pathway controls the expression and activation of Nrf2 in Leishmania amazonensis infection in vitro. Nrf2 activation also required PI3K/Akt signaling and autophagy mechanisms. Nrf2- or PKR/Akt-deficient macrophages exhibited increased levels of ROS/RNS and reduced expression of Sod1 Nrf2-dependent gene and reduced parasite load. L. amazonensis counteracted the Nrf2 inhibitor Keap1 through the up-regulation of p62 via PKR. This Nrf2/Keap1 observation was confirmed in situ in skin biopsies from Leishmania-infected patients. Next, we explored the ex vivo transcriptome in CL patients, as compared to healthy controls. We found the ARE/Nrf2 signaling pathway was significantly upregulated in CL, including downstream target p62. In silico enrichment analysis confirmed upstream signaling by Interferon and PI3K/Akt, and validated our in vitro findings. Our integrated in vitro, ex vivo and in silico approach establish Nrf2 as a central player in human cutaneous leishmaniasis and reveal Nrf2/PKR crosstalk and PI3K/Akt pathways as potential therapeutic targets.